HERMENEUTIKA PEMBAHARUAN LITURGI KONSILI VATIKAN II - Pondaag, Stenly Vianny; Pongoh, Damianus (Department of Theology - Sekolah Tinggi Filsafat Seminari Pineleng, 2025)
This article discussed the hermeneutics of the liturgical reform of the Second Vatican Council. Liturgical reform has been of the most important fruits that the Second Vatican Council produced for the life of the Church. However, the liturgical reform, especially the one of ordo missae, has been one of the most debated issues in the Catholic Church since the Second Vatican Council (1962-1965) until now. The implementation of liturgical reform after the Second Vatican Council was not only welcomed with warm reception, but also with critical attitudes and even rejection. This article showed that the debates and controversies surrounding liturgical reform are rooted in different hermeneutics regarding the Second Vatican Council, and specifically regarding the Constitution of Liturgy. The problem actually arises from two conflicting and contradictory hermeneutics and interpretations. On the one hand there is a so-called hermeneutic of discontinuity and rupture. On the other hand, there is a hermeneutic of reform, or a hermeneutic of renewal in continuity with the one Church.